Concerning Stephen Hawking’s Claim that Philosophy is Dead - Harman, Graham (Filozofski vestnik, 2013)
The article begins from Stephen Hawking's well-known claim that philosophy is dead, and considers several other quotations in which philosophy is either belittled or subordinated outright to the natural sciences. This subordination requires a downward reductionism that is paralleled by the upward reductionism of the linguistic turn and social constructionist theories. Rather than undermining or overmining mid-sized individual entities, philosophy must deal with objects on their own terms. This suggests a possible tactical alliance between philosophy and the arts.